2019
DOI: 10.1016/s1474-4422(19)30147-4
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of co-careldopa as an add-on therapy to occupational and physical therapy in patients after stroke (DARS): a randomised, double-blind, placebo-controlled trial

Abstract: Summary Background Dopamine is a key modulator of striatal function and learning and might improve motor recovery after stroke. Previous small trials of dopamine agonists after stroke provide equivocal evidence of effectiveness on improving motor recovery. We aimed to assess the safety and efficacy of co-careldopa plus routine occupational and physical therapy during early rehabilitation after stroke. Methods This double-blind, multicentre, randomised contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 21 publications
0
24
0
3
Order By: Relevance
“…However, candidate drugs for motor recovery (eg, selective serotonin reuptake inhibitors, levodopa) did not result in significant effects in recent large clinical trials. 58,59 Finally, the various rehabilitation modalities could not be exactly counterbalanced between the groups from EOT to 1-month follow-up, although we investigated the dose of physical and occupational therapies based on patients' recall.…”
Section: Discussionmentioning
confidence: 99%
“…However, candidate drugs for motor recovery (eg, selective serotonin reuptake inhibitors, levodopa) did not result in significant effects in recent large clinical trials. 58,59 Finally, the various rehabilitation modalities could not be exactly counterbalanced between the groups from EOT to 1-month follow-up, although we investigated the dose of physical and occupational therapies based on patients' recall.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence was challenged again in a recent, randomized, large controlled trial of a 6-week continuous dopamine treatment (100 mg levodopa+12.5 mg carbidopa) in addition to standard physical and occupational therapy within 6 weeks after the index event. 41 The results with respect to the relatively crude study endpoint “independent walking ability at 8 weeks” was negative, no surprise at all considering the mixture of stroke and deficit subtypes included in the study: almost 25% lacunar strokes, a variety of anterior circulation strokes, posterior circulation strokes, and even up to 17% of hemorrhages.…”
Section: Examples For Translation Of Therapiesmentioning
confidence: 98%
“…Such functions were, however, not investigated in the recent large randomized trials. In the dopamine trial (DARS) assessment was focused on walking ability 8 weeks after stroke, 41 and in the fluoxetine trial (FOCUS) gross functional outcome was measured by the modified Ranking Scale 6 months after stroke. 24 The latter endpoint is even more incomprehensible with respect to the prior FLAME trial, where the fluoxetine treatment effect was assessed and effective on arm and leg motor function measured with the Fugl-Meyer Motor Scale 3 months after the stroke.…”
Section: Specific Requirements and Pitfalls In Recovery Studiesmentioning
confidence: 99%
“…Several trials of dopamine agonists have reported that these agonists promote motor recovery after stroke [10]. The potential mechanisms of the dopamine-mediated improvement in motor recovery are the potentiation of drive and arousal in conditioned learning and the up-regulation of glutaminergic transmission, which modulates synaptic efficacy [32]. Nevertheless, the clinical effects of pharmacotherapy are limited in stroke patients with severe motor impairment because current motor rehabilitation strategies are focused on the reorganization of preserved motor networks after stroke [33].…”
Section: Discussionmentioning
confidence: 99%